METODE PENGENALAN MEMBACA YANG MENYENANGKAN PADA ANAK USIA DINI - Mutmainah, Mutmainah (MAJALAH ILMIAH PEMBELAJARAN, 2009)
The first three years in children’s life is the most sensitive period which would determine children’s brain development and their future life. The introduction of alphabetical for children could be better done non formally by story telling. The more complex of alphabetical can be introduced for children by the age of 2 years. We can ask the children to name the alphabetical that we showed them. Then, we can improve this exercise by asking them to read word by word. In order to make the exercises (alphabetical introduction and reading the words) are easy to be followed by children, parents should understand how to deliver the exercises properly to the children. Mothers have a significant role to optimize children’s development. They need to give a special attention and time everyday to interact with children using some activities which are effective for children intelligence’s development, without being interrupted with any other activities. One of the example of those activities is by cutting some interesting pictures, could be animal, from magazines or books, then make those pictures as flash cards to be showed to the children. This would have a huge impact for the children’s learning. A working parent needs to monitor and give the correct direction to their nanny or baby sitter about the learning activities when they are not home. It’s simply by making the list of activities so that the baby sitters know what to do everyday to stimulate children’s intelligence development, both intellectual, emotional and their social and physical development. Don’t let the baby sitters to baby sit the children without giving them the stimulations which are significant for children. Some technique that could be used for the reading introduction are using the alphabetical, introducing through things, Montessori School, Finger Painting, Games For Learning, Kinderland method, Flash Card, Story Telling, alphabetical carpet, learning to typing, finishing the incomplete words, and alphabetical posters as the decoration.